Faktor Kesiapan Berwirausaha pada Pelaku UMKM - Tentama, Fatwa; Mulasari, Surahma Asti; Sukesi, Tri Wahyuni; Sulistyawati; Kurniawati; Damaiwanti, Auril; Labiba, Khusna; Qomar, Nurul Izzah Al; Albarusi, Ratna Gumintang; Sari, Melita Putri W. (Universitas Ciputra Surabaya, 2024)
The purpose of this study was to determine the factors that influence entrepreneurial readiness for Micro, Small and Medium Enterprises (MSMEs) in Ngalang Gunungkidul Village. The research method uses qualitative methods with a phenomenology approach. Data collection was taken by conducting semi-structured interviews. The informants in this study were five MSME actors in Ngalang Gunungkidul Village. The analysis used is content analysis technique. The results of the study show that MSME actors have entrepreneurial readiness that comes from individual internal and external factors. Internal factors of entrepreneurial readiness include self-efficacy, risk tolerance, proactivity, need for achievement, independence, future orientation, hardiness, and resilience. External factors of entrepreneurial readiness include education and training, experience, professional network, family background and social support. Both internal and external factors are mutually supportive factors in preparing MSME actors for entrepreneurship, especially after experiencing a decline or loss during the Covid-19 pandemic.